Preparation of Cu0.1-xNixCe0.9O2-y catalyst by ball milling and its CO catalytic oxidation performance. (19th April 2023) - Jiang, Yaxin; Zhang, Dashan; Zhang, Caishun; Han, Jiao; Qing, Shaojun; Liu, Daosheng; Zhang, Lei; Gao, Zhixian
Abstract: A series of Cu0.1-x Nix Ce0.9 O2-y catalysts with different Cu/Ni molar ratios were prepared by the ball milling method. The obtained catalytic materials were characterized by XRD, H2 -TPR, BET, XPS and Ramen and the effects of different Cu/Ni content on the structure, properties and CO catalytic oxidation performance of the catalysts were explored. The results evidenced the formation of Cu–Ni–Ce mixed oxide solid solution in all ternary catalysts. In addition, there is a synergistic interaction between Cu and Ni in ternary catalysts, resulting in more oxygen vacancies and improved reduction performance, and hence demonstrating better CO catalytic oxidation activity in the ternary catalysts than binary ones. Under a GHSV of 60000 mL·gcat −1 ·h −1, the required reaction temperature for reaching less than 10 ppm CO is lowed from 160 °C with Cu0·1 Ce0·9 O2-y to 130 °C with Cu0·07 Ni0·03 Ce0·9 O2-y . Graphical abstract: Image 1 Highlights: Cu–Ni–Ce oxide solid solution can be formed via the ball milling method. The ternary oxide reveals improved CO oxidation activity than binary ones. The best CO oxidation activity is obtained with an optimal Cu/Ni ratio of 7/3. CO can be decreased to less than 10 ppm at 130 °C and 60000 mL·gcat −1 ·h −1 .